CTLA-4–B7 Interaction Is Sufficient to Costimulate T Cell Clonal Expansion - Wu, Yan (The Rockefeller University Press, 1997)
T cell costimulation, particularly by the B7 family members B7-1 and B7-2, plays a critical role in regulating T cell–mediated immunity. Two molecules on T cells, CD28 and CTLA-4, are known to bind to B7. It has been suggested that CD28–B7 interaction promotes T cell response, whereas B7–CTLA-4 interaction downregulates T cell clonal expansion. However, the proposed responses of individual receptors to B7 have not been verified directly. Here, we report that B7-1 promotes clonal expansion of CD28-deficient T cells, and that the CD28-independent costimulatory activity is mediated by CTLA-4, as it is completely blocked by intact and Fab of anti–CTLA-4 mAb. In addition, a mutant B7-1 molecule, B7W88 >A, which has lost binding to CD28 but retained significant CTLA-4 binding activity, promotes T cell clonal expansion. Furthermore, while presence of CD28 enhances T cell response to B7-1, such response is also completely blocked by anti–CTLA-4 mAb. Taken together, our results demonstrate that B7–CTLA-4 interaction promotes T cell clonal expansion, and that optimal T cell response to B7 is achieved when both CD28 and CTLA-4 interact with B7. These results establish an important function of CTLA-4 in promoting T cell activation, and suggest an alternative interpretation of the function of CTLA-4 in T cell activation.